2007
DOI: 10.1016/j.jcrs.2006.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Management of tunnel fungal infection with voriconazole

Abstract: A 59-year-old woman presented 1 month after cataract surgery in the right eye with a stromal infiltrate at the site of the cataract surgery wound. The visual acuity was perception of light with accurate projection. Corneal scraping of the infiltrate revealed septate hyphae. There was no response to 6 weeks of therapy with topical fortified antibiotic agents and topical antifungal therapy in the form of natamycin 5%, amphotericin B 0.15%, and intracameral amphotericin B. The patient was started on oral voricona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The pathophysiology of fungal keratitis after ocular surgery may be attributed to introduction of the organisms directly via surgery, or a delayed breach of the ocular surface via sutures or abnormal epithelium that overlies incisions. 17 Miedziak et al 18 also identified a history of ocular surgery and long-term topical steroid use as pertinent risk factors correlating with a need for penetrating keratoplasty in the management of microbial keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of fungal keratitis after ocular surgery may be attributed to introduction of the organisms directly via surgery, or a delayed breach of the ocular surface via sutures or abnormal epithelium that overlies incisions. 17 Miedziak et al 18 also identified a history of ocular surgery and long-term topical steroid use as pertinent risk factors correlating with a need for penetrating keratoplasty in the management of microbial keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior report by Jhanji et al [3], topical and oral voriconazole was successfully used in the treatment of a fungal tunnel infection not responding to conventional antifungal therapy. Prakash et al [4] reported a series of three cases in which intrastromal voriconazole was used in conjunction with topical treatment for the successful treatment of deep-seated, recalcitrant, fungal keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are some single case studies reporting successful topical voriconazole treatment in fungal keratitis in different clinical circumstances [13,14]. Despite the importance of clinical outcome in cases of fungal keratitis, as demonstrated in several infectious animal models, to our knowledge only one systematic investigation of AH concentrations after different oral voriconazole dosing regimes has been performed [15].…”
Section: Discussionmentioning
confidence: 99%